Performance analysis in top handball matches in the seasons before, during, and after the COVID-19 pandemic - Krawczyk, P.; Szczerba, M.; Labinski, J.; Smolinski, M. (Journal of Sports Analytics, 2024)
The aim of the study was to determine whether there are differences in performance analysis in handball between Pre-COVID-19, during COVID-19, and Post-COVID-19 seasons. The study material was obtained from the official match statistics of PGNiG Super league Ltd. Matches were played in the 2019/2020 season before COVID-19, 2020/2021 during COVID-19, and 2021/2022 Post-COVID-19. The Mann-Whitney U test was used for comparisons between two groups, for three groups using the Kruskal-Wallis test. In Pre-COVID-19 season, players made an average of 1.3 more 9 meter throws the Post-COVID-19. Post-COVID-19 season is characterized by a higher 6 meter goals and 6 meter throw count with respect to the Pre-COVID-19. The results show a higher goalkeeper 7 meter throw effectiveness in Pre-COVID-19 season than in COVID-19. The increasing number of throws and goals from the 6th meter along with a decrease in the number of throws from the 9th meter indicates the latest trends in handball. A reduction in the number of offensive fouls and an increase in the number of fast attacks and the effectiveness of goalkeepers` interventions from 7 meters in the second round of the COVID-19 season indicates the adaptation of players to the new conditions created by the pandemic.